Physiochemical and mineral analysis of honey samples from Varanasi district - MANJU SAHNEY; AJAY KUMAR (International Journal of Pharma and Bio Sciences, 2017)
Honey is a carbohydrate rich bioproduct produced by honeybees from the nectar of flowering plants. Composition of honey depends on the plant species visited by bees, environmental factors, processing and storage conditions. Honey contains sugar, proteins, moisture, vitamins, minerals, enzymes, polyphenols and flavonoides. While foraging, honey bees collect pollen along with the nectar and also receive minerals and heavy metals that plants get from soil, water and air. Determination of physiochemical properties, minerals and heavy metals is important for quality control and certification. Therefore, the present study aims to investigate physiochemical properties ( pH, EC,TDS, ash content, moisture content & colour), minerals (Ca, K, Na, Mg, Fe) and heavy metals (Zn, Pb, Cu, Cd, As) of six honey samples collected from Varanasi district. Among the physiochemical parameters mean values of pH ranged from 3.7 to 4.7, EC from 242±0.08 mS/cm to 1.15±0.16 mS/cm, TDS from 123.5±4.78 ppm to 576.6±81.15 ppm, moisture content from 13.38±0.11% to 21.44±0.21% and ash content 0.125±0.008% to 0.391±0.008%, while colour ranged from light extra amber to dark amber. Among the physiochemical parameters pH, TDS and ash content, were within the limit. EC in one sample and moisture in two samples were higher than the recommended limit by European Commission and Codex Alimentarious. Potassium was the most abundant mineral followed by sodium, calcium, magnesium and iron, Among the heavy metals lead, copper, cadmium, and arsenic were below the limit of detection while Zinc was within the permissible limits. Results indicate that the investigated honey samples are abundant source of minerals essential for human diet, growth and health and also provide indication of environment free from heavy metal in the investigated localities. The study explores good potential of Varanasi district to set up apiary industry for commercial honey production free from heavy metal.